Improving long-lasting insecticidal nets use in Kayange community of North-Western Burundi: a quality improvement study - Habonimana, Desire (My University, 2017)
Introduction TheWorld Health Organization (WHO) reported an estimated global 3.3 billion people still living at risk of malaria in 2015. In the world, only 15 countries bear approximately 80% of malaria related deaths. The Sub-Saharan Africa (SSA) alone accounts for 90% of malaria related deaths. The use of Long-Lasting Insecticidal Net (LLIN) for malaria prevention is a cost-effective intervention. WHO recommends LLIN universal coverage, defined as at least one LLIN for every two people in the household. In SSA and other Low and Middle Income Countries (LMICs), governments and multilateral partners have committed to fully subsidize and provide LLIN for free through mass distribution campaigns. However, LLIN mass distribution has not necessarily led to reduced malaria incidence and related deaths because of its non-use or missed. In Burundi, LLIN is provided free of charge through mass distribution at community level and to pregnant women coming for antenatal care or delivery and childhood immunization. Despite LLIN ownership, Burundi malaria report for 2014 says that only 49% of people sleep under LLIN and only 82% of LLIN are used for their purpose. This has impeded efforts to control malaria and also led to financial wastage. Our study sought to improve LLIN use in Kayange community of north-western Burundi by using the Model For Improvement (MFI). Objective This study assessed the level of LLIN ownership and use in Kayange community of northwestern Burundi with an aim of building on drivers of LLIN non-use in order to identify and test improvement actions by using the MFI. Methods A one group pre-test post-test study design was conducted. LLIN ownership and use was assessed for four weeks before intervention and for another four weeks after intervention. The study was conducted on 96 households in Kayange community of north-western Burundi. The intervention consisted of testing four different weekly small change actions by using the MFI. The first change action consisted of the demonstration of how to mount LLIN and this was conducted at the community yard. The second change action consisted of selecting one watchdog in each household who was tasked of checking and reminding household members to mount LLIN before sleeping. The third change action consisted of conducting two community reminders every week. Reminders were done by a town-crier. The fourth change action consisted of a combination of the last two actions. Data was collected for each week. Descriptive analysis was performed on socio-demographic data and factors associated with LLIN non-use and misuse were summarized using frequency v tables. Each outcome indicator was calculated each week and plotted on a run chart. Results Of the 96 households, 83 (87%) households owned at least one LLIN. However, only 40 (42%) households owned at least one LLIN for every two people. After intervention, the number of LLIN used increased from 32 to 75% (134% increase) and the number of persons (general population) sleeping under LLIN from 35 to 73% (108% increase). The number of children under 5 years sleeping under LLIN increased from 31 to 76% (145% increase) and the number of pregnant women who slept under LLIN from 43 to 73% (69% increase). Also, the averages of the number of nights in each week that the general population slept under LLIN increased from 2.13 to 5.11 (140% increase), children under 5 years slept under LLIN from 1.68 to 4.78 (184% increase) and pregnant women slept under LLIN from 1.56 to 4.47 (186% increase). Conclusion In conclusion, our intervention led to significant increase of all outcome indicators. Drivers of success included community collaboration, an enabling context, and support from stakeholders. Small tests of change at community level have potential of achieving improved outcomes. It is essential to gain collaboration and support from stakeholders and also engage the community.
A research report submitted to the Faculty of Health Science in partial fulfillment of the requirements for the degree of Master of Science (MSc) in Epidemiology - Implementation Science. November, 2017.
Keywords: Insecticidal Nets; Malaria